The Influence of Risk Management on Firm Performance in the Insurance Sector in Indonesia - Wikarsa, Meiliang Gozal; Firmansyah, Fauzi Aldyka Tsaqif; Leon, Farah Margaretha (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of underwriting risk, reinsurance risk, technical provision risk, firm size, and leverage on the financial performance of conventional insurance companies in Indonesia. Financial performance is measured using return on equity. The study applies a quantitative approach using secondary data obtained from the financial statements of insurance companies listed on the Indonesia Stock Exchange during the period of 2020 to 2024, with a total of 200 observations. Panel data regression was employed, and the Hausman test indicated that the fixed effect model was the most appropriate. The results show that firm size has a positive and significant effect on return on equity. Meanwhile, underwriting risk and reinsurance risk have negative but insignificant effects, while technical provision risk and leverage have positive but insignificant effects. These findings suggest that company size plays an important role in increasing profitability, while risk-related variables do not significantly influence financial performance during the observation period.